Assessing Annual and Seasonal Precipitation Trends in the Karun River Basin Using Co-Kriging: An Over 60-Year Analysis - Amin Khoramian (Water Harvesting Research)
The Karun River Basin is an important source of water in Iran, located in a semi-arid region that is under increasing pressure due to changing precipitation patterns. In this work, the trends of precipitation from 1955 to 2019 at 163 meteorological and synoptic stations in the Karun River basin were investigated using the Co-Kriging method to generate precipitation maps for the study period. Although there is no trend in annual precipitation from 1955 to 2019, there is a statistically significant decreasing annual trend at the 10% significance level in the period from 1985 to 2019; -6.6 is the negative slope coefficient. This could indicate a shift towards drier conditions in the latter part of the study period, which affects the availability and management of water resources. The seasonal trends are opposite: a possible decrease in winter precipitation with a slope coefficient of -0.102, indicating drier winters, and a possible increase in fall precipitation, where the slope coefficient is positive at 0.131, indicating wetter autumns. Even though these seasonal trends are not statistically significant with p-values of 0.226 and 0.099, respectively, they underline the complex and dynamic nature of precipitation patterns in the catchment. It is therefore very important to understand the trends of current water resource management strategies and possible future changes in the region to avert the associated risks to irrigated agriculture, domestic water supply, and flood control in this important area.